Caracterização genômica de Salmonella enterica sorotipo Gallinarum biovares Gallinarum e Pullorum associadas a surtos de salmonelose aviária no Brasil - Oliveira, Francisco de Assis de (2022)
Salmonella enterica subsp. enterica serovar Gallinarum biovar Gallinarum (S. Gallinarum) e biovar Pullorum (S. Pullorum) are responsible for infecting mainly young birds causing high mortality leading to serious problems in the poultry industry worldwide. The objective of this work was to report the genomic sequences of S. Gallinarum 4295/02 and S. Pullorum 20811/12 isolated from laying hens in Brazil, and to evaluate the phylogenetic relationship of these bacterial isolates, as well as the presence of potential virulence factors. For this, the genomes were sequenced on an Illumina MiSeq platform. Multilocus sequence typing (MLST), and structural features related to the prediction of virulence genes were determined by bioinformatics analyses. These genomes were grouped into 34 and 36 contigs with 52.2% and 52.1% GC and belong to sequence type 78 (ST78) and 92 (ST92), respectively. 23 Salmonella virulence genes were identified (invA, spaO, spaQ, spaR, spaS , sptP , hilC , hilA , hilD , orgA , sifA , mgtB , mgtC , misL , sipB , sopB , lpfC , spvB, pipB, ssa , ssr , sse , e ssc ) present in the Pullorum biovar, while of these only the genes (sifA, mgtB, mgtC , misL , sopB , pipB , ssa , ssr , sse, and ssc ) were distributed in the Gallinarum biovar. Phylogenetic analysis of the biovars demonstrated distinct clades between S. Gallinarum and S. Pullorum strains suggesting evolutionary events with little evolutionary divergence between the strains The results indicate the occurrence of strains belonging to the studied biovars associated with outbreaks of fowl typhoid and pullorum disease circulating for decades in Brazil. Thus, these data can contribute both to a better characterization of these biovars and to studies on the pathogenicity of Salmonella as well as assisting in future investigations in epidemiological studies.